Specialist butterflies benefit most from the ecological restoration of mires. (April 2016) - Noreika, Norbertas; Kotze, D. Johan; Loukola, Olli J.; Sormunen, Niina; Vuori, Anna; Päivinen, Jussi; Penttinen, Jouni; Punttila, Pekka; Kotiaho, Janne S.
Abstract: Anthropogenic disturbances cause biotic homogenization through the replacement of specialist species with generalists. Restoration has the potential to counteract these negative effects. Recently, restoration in the peatlands of Northern Europe has started to show positive effects on biodiversity. However, seldom have studies evaluated the response of insects to restoration by comparing populations prior to restoration to those thereafter with a Before-After Control-Impact (BACI) design. The aim of this study was to evaluate whether the restoration actions taken were appropriate to facilitate the successful recolonization of mire butterflies and plants. We found that, generally, drainage was negatively associated with mire specialist butterfly species and butterfly and plant communities, while generalist butterflies were not or were positively associated with drainage. In addition, mire specialist butterflies responded negatively to environmental variables associated with drained mires (number of tall trees) and positively to pristine mire-associated variables (larval food plant cover, number of low trees). Although restoration had a significantly positive effect on only two mire specialist butterflies ( Boloria aquilonaris, Colias palaeno ), it had a significantly positive effect on overall specialist species abundance. Furthermore, the structure of the butterfly and plant communities in restored sites became more similar to pristine sites a few years after restoration. We conclude that the restoration actions taken (removing tall trees but leaving smaller trees, and raising the water table level) are appropriate in creating suitable habitat conditions for mire butterflies. Finally, appropriate restoration actions in well-prioritized locations can reverse the trend of biotic homogenization. Highlights: Mire specialist species and communities were negatively associated with drainage. Specialists responded negatively to tall trees, positively to pristine conditions. Restoration had a positive effect on specialist species and community structure. Actions taken are appropriate in creating suitable conditions for mire butterflies. Proper restoration in well-prioritized locations can reverse biotic homogenization.